Evaluation of the Sonas Safe Home Project. Dublin: Sonas Domestic Violence Charity. - Holt, Stephanie (Sonas Housing, 2015)
In 2011, Sonas Domestic Violence Charity1, in conjunction with the Homeless Agency and Dún Laoghaire Rathdown County Council conducted a feasibility study to examine the need for a domestic violence refuge in the Dún Laoghaire Rathdown (DLR) County Council area. This study found that there was broad agreement on the need for emergency refuge accommodation in DLR as part of a wider set of domestic violence service interventions in the area. Given the evidence that a paucity of adequate and affordable housing can prevent women transitioning from domestic abuse situations, the authors concluded that there was a need for the establishment of a number of domestic violence refuges in the area. However, this was considered too costly given the constrained economic climate at that time. Arising from this, Sonas submitted a draft budgeted indication of interest to provide low to medium risk accommodation for victims of domestic violence in August 2011. The Safe Home project was designed to provide both intensive support to women and children and secure crisis accommodation within a community setting in the form of self-contained apartments supported by a mobile Women and Children’s Support Team. The service has four, two bedroom, properties available to it in the DLR County Council catchment area. The Service is available Monday to Friday from 8AM to 6PM with a general on-call service provided outside of these hours. The Dublin Region Homeless Executive (DRHE) and DLR County Council made available €170,000 for the provision of a Safe House scheme on a pilot basis in the local authority area2. Sonas submitted a revised project proposal to the statutory stakeholders in quarter one of 2014.
PUBLISHED
Dublin
Keywords: Domestic violence; Crisis accommodation; Sonas; Inclusive Society; EVALUATION; FAMILY; PROFESSION; Children; Home and community living; Relationships; Social services, interventions and supports